2020
DOI: 10.1002/pssb.201800055
|View full text |Cite
|
Sign up to set email alerts
|

Negative Hygrothermal Expansion of Reinforced Double Arrowhead Microstructure

Abstract: A microstructure, consisting of conventional rods, is herein shown to exhibit “negative hygroscopic expansion” (NHE) in the form of a reinforced double arrowhead with freely rotating joints, whereby the NHE occurs in the direction perpendicular to the reinforcing rods. A kinematic analysis enabled the condition of NHE, as well as the conditions of its “negative thermal expansion” (NTE) analogy, to be established. Results show that the likelihood of “negative expansion” is increased when the longer inclined rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 80 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…Other materials and metamaterials with multinegative properties, i.e., possessing two or more negative properties, have also been explored. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The progress in precision manufacturing, such as 3D printing technology as well as other rapid prototyping techniques, has paved way for even more detailed metamaterials to be designed and analyzed. This progress in precision manufacturing facilitates the development of designed microstructures, i.e., metamaterials, for accurately achieving desired effective properties.…”
Section: Introductionmentioning
confidence: 99%
“…Other materials and metamaterials with multinegative properties, i.e., possessing two or more negative properties, have also been explored. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The progress in precision manufacturing, such as 3D printing technology as well as other rapid prototyping techniques, has paved way for even more detailed metamaterials to be designed and analyzed. This progress in precision manufacturing facilitates the development of designed microstructures, i.e., metamaterials, for accurately achieving desired effective properties.…”
Section: Introductionmentioning
confidence: 99%
“…Double arrow head structure could also show auxetic behavior. [ 47 ] Series of warp knitted fabrics based on double arrow head structure were developed by Alderson et al, [ 26 ] but auxetic behavior of the fabrics was only observed in the diagonal direction. Wang and Hu [ 25 ] successfully fabricated auxetic spacer fabrics using a postcompression and heat setting process.…”
Section: Introductionmentioning
confidence: 99%
“…As such, materials display negative hygrothermal expansion (NHTE) when they demonstrate negative moisture expansion (NME) and/or negative thermal expansion (NTE). Some examples of designed micro-architectures that facilitate NME, NTE and/or negative compressibility (NC) have been made possible by combining materials of non-negative but contrasting expansion coefficients in open-cell micro-truss systems with pin joints or rigid joints [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], bimaterial strips [40][41][42][43][44][45][46] and counterrotating parts [47][48][49]. The category of metamaterials with counter-rotating parts refers to those with scissor-like actions and is a subset of the pin-jointed microstructures.…”
Section: Introductionmentioning
confidence: 99%